An Overview of Quantum Machine Learning Research in China - Luning Li; Xuchen Zhang; Zhicheng Cui; Weiming Xu; Xuesen Xu; Jianyu Wang; Rong Shu (Applied Sciences)
Quantum machine learning (QML) is an emerging discipline that combines quantum computing and machine learning and is able to exhibit exponential superiority over classical machine learning regarding computing speed on specific problems. This article provides a comprehensive review of the QML research in China. The QML development in China is presented in terms of research ideas and tasks, and the algorithms and application fields are sorted out. We have also highlighted some typical creative studies and illuminated their innovation points. Furthermore, the current challenges and future prospects are discussed. This review may provide inspiration for both China’s and global QML-domain progress.